'The house belongs to both': undoing the gendered division of housework. Issue 4 (8th August 2017) - Domínguez-Folgueras, Marta; Jurado-Guerrero, Teresa; Botía-Morillas, Carmen; Amigot-Leache, Patricia
ABSTRACT: This article studies 28 dual-income Spanish childless couples who were undoing gender in routine domestic work. We understand 'undoing gender' as defined by Deutsch [(2007). Undoing gender. Gender & Society, 21, 106–127, p. 122]: 'social interactions that reduce gender difference'. The dual-earner couples came from different socio-economic backgrounds and were interviewed in four different Spanish towns in 2011. The analysis shows that resources in a wide sense, time availability, external help, ideas about fairness, and complex gender attitudes are key interdependent factors that can weave together to form different configurations leading to a non-mainstream division of housework. All configurations were based on principles of gender equality: some couples found it fair to have a 50/50 division of domestic work, others a 50/50 division of all work (paid and unpaid); and a third group showed conflicts in practice. These couples' ways of undoing gender illustrate the external, individual, and couple circumstances under which spouses are able to achieve a non-traditional construction of unpaid work.